(untitled) (Conferencea, 2022)
In the structure of an infertile marriage, the trend towards an increase in the male factor and a deterioration in the quality of sperm dictates the need for a close study of the existing problem. Infertility is a polyetiological disease and requires modern universal markers, the study of the level of which would allow determining the appropriate tactics for managing patients with impaired fertility, assessing the prognosis and prospects for treatment. A biochemical study of the ejaculate makes it possible to assess the activity of the accessory glands of the male reproductive system and the hormonal status of the body as a whole, which is important in assessing the pathology of spermatogenesis